A combined-alpha-shape-implicit-surface approach to generate 3D random concrete mesostructures via digital image processing, spectral representation, and point cloud. (15th July 2017) - Huang, Junjie; Peng, Qi; Hu, Xiaobin; Du, Yunxia
Highlights: An approach to decompose and simulate 2D aggregate shape profiles is suggested. Morphological and spectral characteristics of aggregates are examined. A procedure to represent and simulate 2D microcracks in concrete is developed. A method to construct 3D aggregate point clouds is presented. An algorithm to generate 3D aggregate microstructures is proposed. Abstract: Concrete aggregates have a random and complex shape, which has been shown to affect the mechanical properties of concrete. Commonly, they are approximated as spheres or polyhedra in 3D cases, or further simplified as circles or polygons in 2D cases. This study presents a numerical procedure for the stochastic characterization and representation of the aggregates and microcracks in concrete and the generation of virtual 3D random concrete mesostructures. Central to the proposed simulation method is the generation of realistic 3D aggregate point clouds based on an improved decomposition scheme and the conversion of the point clouds to 3D aggregate microstructures using a hybrid alpha-shape-implicit-surface algorithm. To optimize the simulation results, an image processing procedure and a set of representative aggregates are developed. It is shown that the proposed procedure is capable of reproducing high-quality concrete mesostructures with microcracks, which opens the door to unravelling complex microstructural behaviors of cement-based materials.